WHEAT GERM CELL-FREE TRANSLATION, PURIFICATION, AND ASSEMBLY OF A FUNCTIONAL HUMAN STEAROYL-COA DESATURASE COMPLEX - Goren, Michael A. (2008)
A wheat germ cell-free extract was used to perform in vitro translation of human stearoyl-CoA desaturase in the presence of unilamelar liposomes, and near complete transfer of the expressed integral membrane protein into the liposome was observed. Moreover, co-translation of the desaturase along with human cytochrome b(5) led to transfer of both membrane proteins into the liposomes. A simple, single step purification via centrifugation in a density gradient yielded proteoliposomes with the desaturase in high purity as judged by capillary electrophoresis. After in vitro reconstitution of the non-heme iron and heme active sites, the function of the reconstituted enzyme complex was demonstrated by conversion of stearoyl-CoA to oleoyl-CoA. This simple translation approach obviates the use of detergents or other lipids to stabilize and isolate a catalytically active integral membrane enzyme. The applicability of cell-free translation to the assembly and purification of other integral membrane protein complexes is discussed.